Environmental and Mechanical Evaluation of Blended Cements With High Mineral Admixture Content - Rodrigues, Anna Luiza Macachero Victor; Mendes, Álvaro Ávila Franklin; Gomes, Vanessa; Battagin, Arnaldo Forti; Saade, Marcella Ruschi Mendes; Da Silva, Maristela Gomes (Frontiers in Materials, 2022)
The synergistic effect of combining supplementary cementitious materials (SCMs) as partial substitutes for clinker improves cement properties and reduces its clinker factor and, hence, its carbon footprint. Limestone-calcined clay cement (LC3)—a family of clinker, calcined clay, and limestone filler mixes—is studied worldwide for its properties equivalent to those of Portland cement. Although slag and fly ash are no longer sufficient to keep up with current commercial blended cements, in the long run, these SCMs can support the development of optimized formulations for the future. By relating the environmental and the mechanical performances, the GHG emission intensity offers a broader assessment and selection perspective. In this article, 13 blended cements were evaluated: ternary, quaternary, and multi-admixture (i.e., OPC plus 4 SCMs) blends with clinker factor between 40 and 50%, composed of—in addition to calcined clay and limestone filler—blast furnace slag and fly ash. Compressive strength was measured at 3, 7, 28, 91, and 365 days. The greenhouse gas (GHG) emissions were estimated through life cycle assessment and related to the blends’ compressive strength unit. Quaternary and multi-addition cements consistently outperformed after 3 days of age, demonstrating the benefits of the synergistic effect between SCMs jointly on GHG emissions and compressive strength. Such an effect enables reducing not only the clinker factor and carbon footprint but also the GHG emission intensity, which relates both. This study showed that the formulated cements, particularly those composed of multi-additions (Series D), are potential alternatives for reducing the GHG emissions, whilst preserving mechanical performance demanded by construction market practices. From a multidisciplinary analysis standpoint, durability assessments are necessary to complement the reported findings, as low clinker contents can affect the pH of the concrete’s pore solution and carbonation which ultimately lead to deterioration.